2022
DOI: 10.3991/ijim.v16i06.29001
|View full text |Cite
|
Sign up to set email alerts
|

Hi World: The Virtual Book Learning Integrated Augmented Reality to Increase Knowledge of Covid-19 Prevention in The Learning Process Post-Pandemic Era

Abstract: This research aims to Improve innovation Hi World integrated with AR, Testing The level of attraction of  Hi World, and test the level of Hi World's appropriateness for covid-19 patients. This research method is R&D involving the expert of Covid-19 and digital media. The result from this research are: Innovation of Hi World improved to have a good level of appropriateness with a score of  90%; Level of attraction with this book is good with a score of  95%, and Hi world have design choices that are suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The results showed that the AR learning model was useful for independent learning and motivated students to learn about COVID-19 [10]. Another study developed an AR game to teach primary school students about COVID-19 prevention [11]. The results indicated a significant improvement in student performance from preto post-test and a high usability score, indicating the effectiveness of the AR game in promoting COVID-19 prevention education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the AR learning model was useful for independent learning and motivated students to learn about COVID-19 [10]. Another study developed an AR game to teach primary school students about COVID-19 prevention [11]. The results indicated a significant improvement in student performance from preto post-test and a high usability score, indicating the effectiveness of the AR game in promoting COVID-19 prevention education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the COVID-19 pandemic, universities will have to organize online classes to solve problems [7]- [15]. For the Bachelor of Information Technology at the Faculty of Information Technology, Rajabhat Maha Sarakham University, the adoption of chatbot technology in universities to solve the problem of misinformation for students has been ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In developing technology-based teaching materials, the Ministry of Education and Culture began to be creative through smart books or electronic books, namely BSE (Electronic School Books). However, BSE books only digitize printed books into PDF format, with the presentation of learning content limited to writing/text and image elements only (Putra et al, 2022).…”
Section: Introductionmentioning
confidence: 99%